Eukaryote-conserved histone post-translational modification landscape in Giardia duodenalis revealed by mass spectrometry. Issue 4 (March 2021) - Emery-Corbin, Samantha J.; Hamey, Joshua J.; Balan, Balu; Rojas-López, Laura; Svärd, Staffan G.; Jex, Aaron R.
Graphical abstract: Highlights: Epigenetic regulation is implicated in Giardia development and pathogenesis. Giardia histones have abundant post-translational modifications (PTMs). Many histone PTMs correspond to conserved sites in higher eukaryotes. Co-occurring modifications indicate mechanisms of PTM crosstalk. Annotated chromatin modifier networks highlight dynamic epigenetic regulation. Abstract: Diarrheal disease caused by Giardia duodenalis is highly prevalent, causing over 200 million cases globally each year. The processes that drive parasite virulence, host immune evasion and transmission involve coordinated gene expression and have been linked to epigenetic regulation. Epigenetic regulatory systems are eukaryote-conserved, including in deep branching excavates such as Giardia, with several studies already implicating histone post-translational modifications in regulation of its pathogenesis and life cycle. However, further insights into Giardia chromatin dynamics have been hindered by a lack of site-specific knowledge of histone modifications. Using mass spectrometry, we have provided the first known molecular map of histone methylation, acetylation and phosphorylation modifications in Giardia core histones. We have identified over 50 previously unreported histone modifications including sites with established roles in epigenetic regulation, and co-occurring modifications indicative of post-translational modification crosstalk. These demonstrate conserved histone modifications in Giardia which are equivalent to many other eukaryotes, and suggest that similar epigenetic mechanisms are in place in this parasite. Further, we used sequence, domain and structural homology to annotate putative histone enzyme networks in Giardia, highlighting representative chromatin modifiers which appear sufficient for identified sites, particularly those from H3 and H4 variants. This study is to our knowledge the first and most comprehensive, complete and accurate view of Giardia histone post-translational modifications to date, and a substantial step towards understanding their associations in parasite development and virulence.